Variation of the Ratio Hc3/Hc2 in the Immediate Vicinity of Tc - de la Cruz, F. (1969)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Brown University. Department of Physics; Estados Unidos